Pharmacokinetics, Tolerability, and Safety of Doravirine and Doravirine/Lamivudine/Tenofovir Disoproxil Fumarate Fixed-Dose Combination Tablets in Adolescents Living With HIV: Week 24 Results From IMPAACT 2014. (1st February 2023) - Melvin, Ann J.; Yee, Ka Lai; Gray, Kathryn P.; Yedla, Mounika; Wan, Hong; Tobin, Nicole H.; Teppler, Hedy; Campbell, Havilland; McCarthy, Katie; Scheckter, Rachel; Aurpibul, Linda; Ounchanum, Pradthana; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: We studied the pharmacokinetics (PK) and safety of 100-mg doravirine and doravirine/lamivudine/tenofovir disoproxil fumarate fixed-dose combination (100/300/300 mg DOR FDC) treatment in adolescents with HIV-1. Methods: Adolescents ages 12 to younger than 18 years were enrolled in 2 sequential cohorts. Cohort 1 evaluated intensive PK and short-term safety of 100-mg single-dose doravirine in adolescents ≥35 kg. Cohort 2 participants either initiated treatment with DOR FDC (antiretroviral (ARV)-naïve) or switched to DOR FDC from a previous ARV regimen (virologically suppressed). The first 10 Cohort 2 participants had intensive PK evaluations, and safety, sparse PK, and HIV RNA were assessed through week 24. Results: Fifty-five adolescents, median age 15.0 years and baseline weight 51.5 kg, were enrolled. Nine participants completed Cohort 1 PK assessments (8 of the 9 participants weighed ≥45 kg) and 45 initiated study drug in Cohort 2. The doravirine geometric mean (GM) AUC0–∞ was 34.8 μM∙hour, and the GM C24 was 514 nM after a single dose, with a predicted steady-state GM C24, ss, pred of 690 nM. Cohort 2 enrolled adolescents weighing ≥45 kg. Plasma concentrations of doravirine, tenofovir, and lamivudine achieved by Cohort 2 participants were similar to those reported in adults. No drug-related serious or grade 3 or 4 adverse events occurred. Forty-two of 45 participants (93.3%; 95% CI: [81.7, 98.6]) achieved or maintained HIV-1 RNA <40 copies/mL. Conclusions: Doravirine and DOR FDC achieved target PK in adolescents with HIV-1. DOR FDC was well-tolerated and maintained excellent virologic efficacy through 24 weeks, offering a favorable option for adolescents.